The heat capacity and entropy of the lithium silicides Li17Si4 and Li16.42Si4 in the temperature range from (2 to 873) K. (June 2015) - Thomas, Daniel; Zeilinger, Michael; Gruner, Daniel; Hüttl, Regina; Seidel, Jürgen; Wolter, Anja U.B.; Fässler, Thomas F.; Mertens, Florian
Highlights: High quality experimental heat capacities of the new lithium rich silicides Li17 Si4 and Li16.42 Si4 are reported. Two different calorimeters have been used to cover the broad temperature range from (2 to 873) K. Samples were prepared and characterized (XRD) by the original authors who firstly described these new silicide phases in 2013. Supply of polynomial heat capacity functions for four temperature intervals. Calculation of standard entropies and entropies of formation of the lithium silicides. Abstract: This work presents the heat capacities and standard entropies of the recently described lithium rich silicide phases Li17 Si4 and Li16.42 Si4 as a function of temperature in the range from (2 to 873) K. The measurements were carried out using two different calorimeters. The heat capacities were determined in the range from T = (2 to 300) K by a relaxation technique using a Physical Properties Measurement System (PPMS) from Quantum Design, and in the range from T = (283 to 873) K by means of a Sensys DSC from Setaram applying the Cp -by-step method. The experimental data are given with an accuracy of (1 to 2)% above T = 20 K and the error increases up to 7% below T = 20 K. The results of the measurements at low temperatures permit the calculation of additional thermodynamic parameters such as the standard entropy as well as the temperature coefficients of electronic and lattice contributions to the heat capacity. Additionally, differential scanning calorimetric (DSC) measurements were carried out to verify the phase transition temperatures of the studied lithium silicide phases. The results represent a significant contribution to the data basis for thermodynamic calculations ( e.g. CALPHAD) and to the understanding of the phase equilibria in the (Li + Si) system, especially in the lithium rich region.